Understanding the Adhesion Mechanism of Conventional Denture Adhesives - Khadivi, Nona. (2017)
Abstract: Denture adhesives are widely used to avoid the detachment and sliding of dentures. However, their adhesion properties can be affected by variation in mouth condition and underlying conditions such as level of salivation. The objective of this study is to understand the mechanisms governing the properties of a commercially available denture adhesive and identifying the reasons for the observed variation in its adhesion strength. In vitro models mimicking the denture gingival interface are designed to evaluate the performance of the adhesive. Changes in adhesion strength in response to three major factors related to the oral conditions including level of salivation, pH, and temperature are measured. The results of lap-shear, tensile test and internal interactions suggested a cohesion failure, where the lowest adhesion strength was due to hyposalivation. Fourier transform infrared spectroscopy (FTIR) and rheological analysis confirmed various involved mechanisms in governing the adhesion characteristics of the paste. We observed that the incorporation of tripropylene glycol methyl ether (TPME) to enhance hydrogen bonding could significantly improve adhesion in hyposalivation scenario.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Irene Georgakoudi.; Committee: Irene Georgakoudi, David Kaplan, and Ali Tamayol.; Keywords: Biomedical engineering, and Dentistry.